PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS DAN SIMPLE ADDITIVE WEIGHTING UNTUK PEMILIHAN SUPPLIER TOKO BERAS - Syahputra, Angga; Diana, Anita; Achadiani, Dwi (IDEALIS : InDonEsiA journaL Information System, 2024)
The supplier selection process is an important thing in the procurement of products and services. Decision Support System (SPK) designed, it can help select the best supplier at the Matondang Rice Store, and is expected to be able to provide recommendations for selection results that can be accepted by shop owners, based on the criteria that have been applied. The owner shop doesn’t have a criterion weight value so it is difficult to determine the best supplier for the Matondang Rice Store where the selection is still subjectivity and not objective. The owner of the Matondang Rice Store doesn’t have a structured report where there is no supplier data report, ranking report and supplier assessment report, so it is difficult to see the value of each supplier who cooperates with the Matondang Rice Store. SPK was created that can solve these problems. Researchers determined the use of the Analytical Hierarchy Process (AHP) method for weighting criteria values and used the Simple Additive Weighting (SAW) method to determine the final result in the form of alternative supplier rankings. This research through the AHP method produces weighted values of Price, Quality of Products, Availability of Products, Service, Delivery Time, is 0.245 0.092, 0.325, 0.060, 0.278. Then through the SAW method, Patriot Missile Shop got the highest score with a number of 0.970. The Patriot Missile Shop is the best supplier according to the Matondang Rice Store. This SPK can provide recommendations for selected suppliers more objectively for rice shop owners.